Circulating Cholesterol Levels May Link to the Factors Influencing Parkinson’s Risk - Zhang, Lijun; Wang, Xue; Wang, Ming; Sterling, Nick W.; Du, Guangwei; Lewis, Mechelle M.; Yao, Tao; Mailman, Richard B.; Li, Runze; Huang, Xuemei (Frontiers in Neurology, 2017)
Objectives: A growing literature suggests that circulating cholesterol levels have been associated with Parkinson’s disease. In this study, we investigated a possible causal basis for the cholesterol-PD link. Methods: Fasting plasma cholesterol levels were obtained from 91 PD and 70 age- and gender-matched controls from an NINDS PD Biomarkers Program cohort at the Pennsylvania State University College of Medicine. Based on the literature, genetic polymorphisms in selected cholesterol management genes (APOE, LDLR, LRP1, and LRPAP1) were chosen as confounding variables because they may influence both cholesterol levels and PD risk. First, the marginal structure model was applied, where the associations of total- and LDL-cholesterol levels with genetic polymorphisms, statin usage, and smoking history were estimated using linear regression. Then, potential causal influences of total- and LDL-cholesterol on PD occurrence were investigated using a generalized propensity score approach in the second step. Results: Both statins (p<0.001) and LRP1 (p<0.03) influenced total- and LDL-cholesterol levels. There also was a trend for APOE to affect total- and LDL-cholesterol (p=0.08 for both), and for LRPAR1 to affect LDL-cholesterol (p=0.05). Conversely, LDLR did not influence plasma cholesterol levels (p>0.19). Based on propensity score methods, lower total- and LDL-cholesterol were significantly linked to PD (p<0.001 and p=0.04, respectively). Conclusions: The current study suggests that circulating total- and LDL-cholesterol levels potentially may be linked to the factor(s) influencing PD risk. Further studies to validate these results would impact our understanding of the role of cholesterol as a risk factor in PD, and its relationship to recent public health controversies.